Correction: Leishmania infantum isolates exhibit high infectivity and reduced susceptibility to amphotericin B. Issue 8 (6th August 2020) - Faral-Tello, Paula; Greif, Gonzalo; Satragno, Dinora; Basmadjián, Yester; Robello, Carlos
Abstract : Correction for ' Leishmania infantum isolates exhibit high infectivity and reduced susceptibility to amphotericin B' by Paula Faral-Tello et al., RSC Med. Chem., 2020, DOI: ; 10.1039/d0md00073f .